Castles, siegeworks and settlements : surveying the archaeology of the twelfth century - Wright, Duncan W.,; Creighton, O. H. 1972- (Archaeopress Publishing Ltd, 2016)
This volume comprises thirteen reports detailing fieldwork undertaken by a research project which sought to assess the archaeological evidence of the period of conflict that took place in mid-twelfth-century England popularly known as `the Anarchy'.